‘We are nature defending itself’—The Forest of Dannenrod Occupation as an Example of Contested Extractivism in the Global North - Dorothea Hamilton; Sina Trölenberg (Revue Internationale de Politique de Développement)
Extractive activity is not limited to mining; it also occurs in the other forms of large-scale landscape destruction, including the deforestation involved in extensive infrastructure projects. Yet while resistance to activities such as fracking and coal mining has been intensively investigated within the extractivism debate under the collective term ‘contested extractivism’, resistance to the extraction of renewable parts of nature such as woodland has, by comparison, been somewhat neglected. Likewise, the academic debate has focused mostly on case studies from the global South. We argue that opposition to the felling of more than 85 hectares of woodland in the Forest of Dannenrod (Germany) for the construction of a highway is an example of contested extractivism in the global North. We portray the protest as a clash between extractivist and anti-extractivist notions in Europe, the latter partly transitioning into post-extractivist imaginaries. And although the area was felled in 2020, we argue that this opposition marked a turning point for the German environmental justice movement and sparked a national debate, despite persistent support mechanisms for wood extraction and negative media reports.